1953
DOI: 10.21236/ada278404
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic Viscous Flow on Noninsulated Flat Plate

Abstract: An analytical treatment of the "strong" interaction problem in hypersonic viscous flow on a noninsulated flat plate is presented, using the method of "similar" solutions of the compressible boundary layer equations. Recent experimental data which confirm some of the theoretical results are also discussed. 1 2 yi(w-local heat transfer coefficient Ch.= p.uHG Rex i Po UX free stream Reynolds number on the Rex 9 .0basis of x A,B,C,D defined in Eqs 16-19 .w exponent in the viscosity law Subscripts 'o", I1', wo", aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1959
1959
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…the induced pressure is 10 times the free stream value ahead of the flat plate. The skin friction and heat transfer (13) for the plate will be much higher for this flow condition compared with values determined by the compressible boundary layer without pressure gradient. The results for flow Mach 15.6 lie between the induced pressure results for flow Mach 9.77 and 19.6.…”
Section: Shock Wave-boundary Layer Interaction Induced Pressure Distrmentioning
confidence: 66%
See 2 more Smart Citations
“…the induced pressure is 10 times the free stream value ahead of the flat plate. The skin friction and heat transfer (13) for the plate will be much higher for this flow condition compared with values determined by the compressible boundary layer without pressure gradient. The results for flow Mach 15.6 lie between the induced pressure results for flow Mach 9.77 and 19.6.…”
Section: Shock Wave-boundary Layer Interaction Induced Pressure Distrmentioning
confidence: 66%
“…The other solutions (10)(11)(12) were derived on the assumption that the boundary layer and the shock wave were distinctly separated, even in the vicinity of the leading edge. A theoretical result for the hypersonic viscous flow over a noninsulated flat plate has been derived in (13). Recent experimental results (1,2) for a flat plate with a sharp leading edge have indicated that the shock wave and the boundary layer are merged for some distance back of the leading edge before separating.…”
Section: Hypersonic Shock Wave-boundary Layer Interaction and Leadingmentioning
confidence: 99%
See 1 more Smart Citation
“…This data resulted from Preston tube measurements and was obtained only at the two values of x at which the complete flowfield profiles were taken. Again the present analysis, as well as the analyses of Eckert 17 and Li and Nagamatsu, 18 are included for comparison. The present theory is observed to compare quite favorably at higher values of % with the strong interaction theory, and at lower x it approaches the boundary-layer predictions of Eckert.…”
Section: Presentation and Discussion Of Resultsmentioning
confidence: 99%
“…8 They arrived at their approach after Reasonable agreement was obtained between computed results and experimental heat flux data for a favorable pressure gradient over a blunted flat plate. The Bertram and Feller method was modified by Crawford to accommodate a more general pressure profile.…”
Section: Introductionmentioning
confidence: 99%